al-Qaḍāʾ wa-'l-quḍā fī Barqa wa-Ṭarābulus munḏu al-fatḥ al-ʿArabī ilā maṭlaʿ al-qarn al-ḫāmis al-Hiǧrī - Abū-Dīb, aṣ-Ṣaid (al-Muʾassasa al-ʿĀmma liṯ-Ṯaqāfa, 2009)
Law and Judges; Cyrenaica and Tripoli; history